Prevalence of Hepatitis A Virus (HAV) and Hepatitis E Virus (HEV) among Febrile Patients with Gastrointestinal Symptoms: A Prospective Study in A Tertiary Care Hospital - Baig, Habeeb Ali; Patel, Sadhineni Srinath; Sultana, Waseema; Elhaj, Abdelrhman; Elhag, Musa; Ali, Sarah; Srinath, Mote (Journal of Neonatal Surgery, 2025)
Introduction: The prevalence of enteric hepatotropic viruses, such as hepatitis A virus (HAV) and hepatitis E virus (HEV), is influenced by the level of sanitation in a given area. Aim: This study aimed to determine the prevalence of HAV and HEV in febrile patients presenting with symptoms of diarrhoea and persistent vomiting. Methods: A prospective study was conducted at a tertiary care hospital, where 328 febrile patients were included. Blood samples were collected and serum was separated and analysed for specific HAV and HEV antibodies using ELISA (Enzyme Linked Immuosorbent Assay). Results: Out of 328 patients, tested for HAV IgM 24(7.3%) and HEV IgM 04(1.2%) were tested positive. The higher prevalence was observed in females than in males for both HAV and HEV infection, and the cases were eminent during monsoon season. Conclusion: The present study, underscores the importance of the early diagnosis to prevent the outbreaks in communities